The Effect of Problem Solving - Focused Coping Skill Towards Stressed Nurses with Extrovert and Introvert Personality - Reny Rahmawati, Wiwin; Sugiarto, Angga (International Journal of Psychosocial Rehabilitation, 2020)
Stress is a phenomenon that cannot be avoided by individuals, including nurses. Nurses—responsible for taking care of patients—in various health care units will be faced with different conditions that can trigger stress. Several previous studies mentioned that the stress levels of nurses are in the high category. Nurses with a high-stress level will decrease the quality of their work. Therefore, nurses need to practice using appropriate coping strategies; one of them is problem-solving-focused coping skills to cope with the stress. Some research indicates a strong correlation between stress and coping strategies with the nurse’s personality. This research is to determine the effect of problem-solving-focused coping skills on stressed nurses with extroverted and introverted personalities. This research was using a quasi-experiment with a randomized two-group design. Samples were selected through simple random sampling, starting with choosing the location of the workplace randomly, then screening using the ISMA instrument to determine the level of stress, and the PSI instrument to determine the personality type of nurses. 22 samples fulfill the inclusion and exclusion criteria divided into 2 groups of extroverts and introverts. In this study, subjects are controlled through blood cortisol levels examination in pre- and post-intervention—aside from the ISMA questionnaire—to determine the differences in decreased levels of stress before and after intervention. Result The results showed a significant difference between the scores of stress before and after treatment in both groups, through the t-test with t-value value 10.647 and p-value of 0.000 on an extrovert group, then the t-value value 6.130 and p-value 0.000 on introvert group. He has accepted that problem-solving skills-focused coping affects the stress of nurses with extroverted and introverted personality.